Recommendations for the content and conduct of European League Against Rheumatism (EULAR) musculoskeletal ultrasound courses. Issue 7 (5th October 2007) - Naredo, E; Bijlsma, J W J; Conaghan, P G; Acebes, C; Balint, P; Berner-Hammer, H; Bruyn, G A W; Collado, P; D'Agostino, M A; de Agustin, J J; de Miguel, E; Filippucci, E; et al.
Abstract : Objective: To develop education guidelines for the conduct of future European League Against Rheumatism (EULAR) musculoskeletal ultrasound (MSUS) courses. Methods: We undertook a consensus-based, iterative process using two consecutive questionnaires sent to 29 senior ultrasonographer rheumatologists who comprised the faculty of the 14th EULAR ultrasound course (June 2007). The first questionnaire encompassed the following issues: type of MSUS educational model; course timing; course curriculum; course duration; number of participants per teacher in practical sessions; time spent on hands-on sessions; and the requirements and/or restrictions for attendance at the courses. The second questionnaire consisted of questions related to areas where consensus had not been achieved in the first questionnaire, and to the topics and pathologies to be assigned to different educational levels. Results: The response rate was 82.7% from the first questionnaire and 87.5% from the second questionnaire. The respondents were from 11 European countries. The group consensus on guidelines and curriculum was for a three-level education model (basic, intermediate and advanced) with timing and location related to the annual EULAR Congresses. The topics and pathologies to be included in each course were agreed. The course duration will be 20 h. There will be a maximum of six participants per teacher and 50–60% of total time will be spent on practical sessions. There was also agreement on prerequisite experience before attending the intermediate and advanced courses. Conclusion: We have developed European agreed guidelines for the content and conduct of EULAR ultrasound courses, which may also be recommended to national and local MSUS training programmes.